Implementasi Sistem Informasi Akuntansi Dan Akuntabilitas Pengelolaan Dana Bos Reguler - Nurul Farida; Mulyaningtyas (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2024)
This study aims to find out and evaluate whether the Implementation of Accounting Information Systems and Accountability for Regular School Operational Assistance (BOS) at SMP Plus Hidayatul Mubtadiin Singosari is by